[tex]Efectuati:
a) \frac{2x+1}{x-2}+ \frac{1-2x}{x+2}+ \frac{x^{2}+16}{ x^{2} -4} =
b) \frac{x-2}{x+1} + \frac{x+3}{x+2}+ \frac{5- x^{2} }{ x^{2}+3x+2 } =
[/tex]
Răspunsuri la întrebare
Răspuns de
1
a. [ ( 2x +1)· ( x +2) + ( x -2) ·( 1 -2x) + x² + 16 ] / ( x² - 4)
= [ 2x² + x + 4x + 2 + x - 2 - 2x² + 4x + x² + 16 ] / ( x² - 4)
= [ x² + 10x + 16 ] / ( x² - 4) = ( x + 2) · ( x + 8 ) / ( x + 2)· ( x -2)
= ( x + 8 ) / ( x - 2)
b. = [ ( x -2) · ( x + 2) + ( x +3 )·( x+ 1) + 5 - x² ] / ( x + 1)· ( x + 2)
= [ x² - 4 + x² + 4x + 3 + 5 - x² ] / ( x +1) · ( x +2)
= [ x² + 4x + 4 ] / ( x +1) · ( x +2)
= ( x + 2) ² / ( x +1) · ( x +2)
= ( x + 2) / ( x +1)
= [ 2x² + x + 4x + 2 + x - 2 - 2x² + 4x + x² + 16 ] / ( x² - 4)
= [ x² + 10x + 16 ] / ( x² - 4) = ( x + 2) · ( x + 8 ) / ( x + 2)· ( x -2)
= ( x + 8 ) / ( x - 2)
b. = [ ( x -2) · ( x + 2) + ( x +3 )·( x+ 1) + 5 - x² ] / ( x + 1)· ( x + 2)
= [ x² - 4 + x² + 4x + 3 + 5 - x² ] / ( x +1) · ( x +2)
= [ x² + 4x + 4 ] / ( x +1) · ( x +2)
= ( x + 2) ² / ( x +1) · ( x +2)
= ( x + 2) / ( x +1)
getatotan:
ok
Alte întrebări interesante
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă